Academic Quality Culture: Influence on Student Learning Concentration through Learning Management System-Based Classroom Management - Mohamad Shepna Giantama; Reza Ifnuari; Neti Karnati; Desi Rahmawati; Aldo Redho Syam (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2026)
This research is aimed at investigating the effect of academic quality culture on student learning concentration with LMS-based classroom management as an intervening variable in higher education. There is a signficant amount of research on academic quality and digital learning environments. However little empirical evidence exists to cliffhanger how the institutional culture of quality manifests through technology-mediated pedagogical practices in shaping attentional engagement. Based on a quantitative survey design using Structural Equation Modeling (SEM) with SmartPLS, the study obtained data collected from 391 undergraduate students of Faculty of Teacher Training and Education, Universitas Pakuan Bogor, Indonesia through proportionate stratified random sampling represented by six study programs. Academic quality culture (30 items, α = 0.91), LMS-based classroom management (28 items, α = 0.89), and learning concentration (30 items, α = 0.93) were measured with validated instruments. The results demonstrate that the effect of academic quality culture on learning concentration (β = 0.34, p < 0.01) and LMS-based classroom management (β = 0.52, p < 0.01) is direct for both types of effects in this model LMS-based classroom management has a positive impact on learning concentration (β = 0.41, p < 0.01), which partially mediates the relationship between academic quality culture and learning concentration (indirect effect = 0.213, p < 0.01). The variance explained in learning concentration is 58.6% by the model. The results indicate that developing a high-quality academic culture promotes student attention directly and indirectly as well, by enhancing pedagogical management via LMS. Implication of this study contributes an innovative integrative framework connecting institutional quality culture, classroom management, cognitif learning outcomes, and student learning concentration at higher education in Indonesia.